1996
DOI: 10.1007/bf02207277
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent alteration of rat cardiac sodium current by isoproterenol: Results from direct measurements on multicellular preparations

Abstract: Conflicting results have been reported in literature about the influence of beta-adrenergic stimulation on the fast cardiac sodium current (INa+). To elucidate these mechanisms in multicellular preparations we used the loose-patch-clamp technique to evaluate the effect of the beta-adrenergic agonist isoproterenol 1-1000 nmol/l. Isoproterenol enhanced INa+ at all membrane potentials by elevation of the maximal available INa+ . Only at the high concentration of 1 micromol/l was INa+ slightly depressed after depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…This limitation was partially overcome by a modification of the cell-attached patch-clamp recording 42 , the loose patch clamp 21,22,43 . This technique has been used to measure ionic currents in multicellular cardiac preparations such as trabeculae and papillary muscle 44,45,46 . However, none of these reports was performed on an intact perfused heart during a physiological triggered AP.…”
Section: Discussionmentioning
confidence: 99%
“…This limitation was partially overcome by a modification of the cell-attached patch-clamp recording 42 , the loose patch clamp 21,22,43 . This technique has been used to measure ionic currents in multicellular cardiac preparations such as trabeculae and papillary muscle 44,45,46 . However, none of these reports was performed on an intact perfused heart during a physiological triggered AP.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the β 1 -adrenergic signaling system with isoproterenol leads to an increase in the amplitude of I Na , however, without the effects on gating properties of the channel [84], [85]. Simultaneous activation of several components of the β 1 -adrenergic signaling system with cAMP-IBMX-forskolin cocktail or with excessive application of membrane permeant analogue of cAMP, CPTcAMP (5 mM), results in additional small shift in the G/G max and steady-state inactivation [86], [87], [88].…”
Section: Methodsmentioning
confidence: 99%
“…Panel C: An increase in peak I Na availability upon application of different concentrations of isoproterenol (in %). Experimental data by Kirstein et al [84] obtained from rat ventricular myocytes are shown by black bars with errors; corresponding simulation data are shown by gray bars. Peak current-voltage ( Panel D ) and steady-state inactivation ( Panel E ) relationships for the fast Na + current in ventricular myocytes upon stimulation with 0.1 µM isoproterenol.…”
Section: Methodsmentioning
confidence: 99%
“…However, the effects of isoprenaline on sodium-channel currents have not been resolved completely. Some studies have shown that sodium channels can be modulated via multiple mechanisms, including both direct and indirect pathways [1][2][3][4][5] . The direct mechanism of regulation, which is protein kinase A (PKA)-independent, increases sodium current without alternation of the single-channel characteristics and without shifting the activation of the voltage-dependent current.…”
Section: Introductionmentioning
confidence: 99%